Development of in vitro and in vivo models to characterize biofilm formation by a necrotizing strain of Group A Streptococcus - Anuradha Vajjala (2017)
Group A Streptococcus (GAS) causes a wide variety of human diseases, ranging from mild, self-limiting infections to highly invasive life-threatening diseases such as necrotizing fasciitis (NF) and streptococcal toxic shock syndrome (STSS). In accordance, GAS is the fourth most common bacterial cause of human morbidity and mortality, accounting for more than half a million deaths annually. In recent years, a few molecular determinants and pathways that regulate GAS biofilm formation have been identified, based on various in vitro and a few in vivo models. However, we lack information as to whether the mechanisms identified have clinical relevance for biofilm-associated infection, especially acute infection. Biofilm is thought to play a role during GAS colonization of epithelial cells and structures of microcolonies were observed in the fascia of NF patients. Yet, the role of these aggregates in GAS infections remains uncertain. In this study, we establish and characterize an in vitro model of GAS biofilm formation on mammalian cells and further validate our findings in an in vivo mouse model of human soft tissue infection. We found that GAS forms dense aggregates on a variety of epithelial cells that display biofilm characteristics, including a 3D architecture, extracellular matrix, enhanced tolerance to antibiotics and late stage biofilm dispersal. In contrast to GAS biofilm on abiotic surfaces, host-associated biofilm required the expression of GAS secreted toxins streptolysins O and S (SLO, SLS). These toxins trigger endoplasmic reticulum (ER) stress that leads to host cell apoptosis and necrosis. Further, during the early stages of biofilm development, GAS SLO and SLS induced cell death cascade results in the release of a host-associated factor that augments subsequent biofilm development on necrotic mammalian cells. Supernatants from GAS-infected mammalian cells or from cells treated with ER stressors restored biofilm formation of a streptolysin null mutant that is otherwise attenuated in biofilm formation on mammalian cells. Similar behavior was detected in a mouse model of GAS soft tissue infection. While wild type GAS formed dense aggregates that concentrated mainly in the fascia and subsequently spread beyond the initial infection site, the streptolysin null mutant formed considerably fewer microcolonies and the infection was confined to the site of infection, without progressing into deeper tissues. Most striking, pre-treatment of the infection site with the ER stress-inducing drug thapsigargin restored the ability of the streptolysin null mutant to cause wild type-level infection. Taken together, I have demonstrated a novel role for streptolysins SLO and SLS mediated ER stress that plays a major role in in vitro and in vivo GAS biofilm formation and disease progression.